Risk factors for mortality in delayed intertrochanteric fractures - Haluk Cabuk; Cem Dincay Buyukkurt; Ali Cagri Tekin; Suleyman Semih Dedeoglu; Yunus Imren; Yasin Guler; Hakan Gurbuz (Medicine Science, 2017)
We aimed to figured out the risk factors of one year mortality in intertrochanteric hip fractures with delayed operation more than 72 hours. 96 out of 226 patients with proximal femoral fracture included in this study. Hemogram, blood urine nitrogen (BUN), creatinine, sodium, potassium and serum albumin levels are recorded from their blood test at administration of hospital. Time to theatre and postoperative needs for intensive care are recorded. Mobility functions before fracture and after 3 months of operation are assessed by mobility part of Barthel index. Multiple logistic regression analysis was performed to estimate the simultaneous effects of important covariates. In univariate model, age(p=0.0027), ASA(p=0.00), loss of mobility(p=0.00), bone union time(p=0.001), blood transfusion(p=0.026), albumin(p=0.004) and mobility after operation (p=0.001) were associated with mortality but in the final model for multivariate regression analysis loss of mobility level (p=0.001) and bone union time (p=0.02) were found to be independent risk factors of mortality. In postoperative period mobilization is the most important variable that we could changed in intertrochanteric fractures to decrease mortality. Whatever the timing of operation, gaining the mobility as soon as possible should be the goal of our treatment. [Med-Science 2017; 6(3.000): 521-5]